Corporate social responsibility stimulus on environmental problems: Spatial threshold model analysis - Wang, Yu; Ahmad, Saleem; Waseem, Liaqat Ali; Akhter, Sonia; Jihane, Mokhchy (PloS one, 2023)
A popular subject of general interest is the connection between corporate social responsibility, research and development, tax policy, and the purchase of green bonds. To encourage the coordinated growth of the economy and a pollution-free environment, it is crucial to understand how they interact. The paper develops a theoretical framework based on the general equilibrium theory’s multi-sector model to examine how tax competition affects environmental degradation. The existence of such an effect, which is a threshold effect resulting from corporate social responsibility (CSR), and how it is impacted by CSR are theoretically established. The study used Moroccan province panel data from 2000 to 2022 and the spatial panel threshold model. The empirical finding demonstrates the importance of the threshold impact of CSR since reduced tax competition tends to worsen environmental degradation when CSR is above the threshold value and to reduce it when CSR is below the threshold value. The study also reveals that the impact of tax competitiveness varies regionally. Several policy suggestions are then put out to assist Morocco in reducing environmental pollution through taxation.